An unusual lung mass post stem cell transplantation. Issue 4 (4th July 2014) - Lyons, J.; Vandenberghe, E.; Fahy, R.; McDonnell, C.; Keane, J.; McLaughlin, A.M.
Abstract We report a case of Mycobacterium kansasii presenting as an obstructing endobronchial mass in a patient post stem cell transplant. The patient had a complete clinical, microbiological, and radiological response to anti‐tuberculous treatment. To our knowledge, this is the first case of M. kansasii presenting post transplant with an obstructing lung mass simulating relapse or post‐transplant lymphoma.